2020
DOI: 10.1002/maco.202011516
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH on corrosion behavior of carbon steel in simulated cooling water containing scale and corrosion inhibitors

Abstract: In this paper, the influence of pH on the corrosion behavior of AISI 1020 carbon steel in simulated cooling water was investigated by using electrochemical and surface analysis methods. The results of polarization showed that the corrosion resistance of carbon steel increased with an increase in pH of the simulated water, and the corrosion control process changed from cathodic polarization to anode polarization control. The scale and corrosion inhibitor 2‐phosphonobutane‐1,2,4‐tricarboxylic acid (PBTCA) had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…For example, mechanical properties should be tested by measuring the tolerance of stretch and press 100 . In addition, the pH or concentration of the aqueous electrolytes should also be in situ investigated for the change and the optimal solution 101 …”
Section: Advanced Characterization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, mechanical properties should be tested by measuring the tolerance of stretch and press 100 . In addition, the pH or concentration of the aqueous electrolytes should also be in situ investigated for the change and the optimal solution 101 …”
Section: Advanced Characterization Methodsmentioning
confidence: 99%
“…Fu et al built a modified Znmetal anode surface via Sn flakes retexturing as shown in Figure 2C. Compared to the Zn/Sn (101) and the bare Zn, the preferential orientation of Zn/Sn (200) not only contributes to the lower deposition energy barrier, which promotes Zn deposition kinetics but also induces the lateral growth of Zn crystals. 54 Benefiting from the strong points, the Zn/Sn (200) shows lower voltage hysteresis of about 20 mV, as well as a better cycle lifetime over 500 h at 1 mA cm −2 with the restrained Zn dendrite formation.…”
Section: Modified Zn Substratementioning
confidence: 99%
“…At specific pH values, the OLE may exhibit greater potential in generating a protective film on the metal surface. many studies revealed that when decreasing the pH from 8 to 3.9, different changes were observed in the corrosion potential after adding the inhibitor and that the efficiency of the inhibitor decreases with increasing acidity, and also the weight loss decreases with increasing the pH from 3.15 to 8.0 22 , 23 It was noticed in the practical results that as the acidity of the solution increased and the pH decreased, the effectiveness of the extract decreased. Therefore, comprehending the correlation between pH and its impact on the efficacy of OLE as a corrosion inhibitor is of utmost importance in optimizing its usage.…”
Section: Introductionmentioning
confidence: 99%